When in Aotearoa Do as the Kiwis Do (Comparative & International Education Series, 2022)
Although five years have passed, what happened in the last trimester of my master’s study in New Zealand has always reminded me not to take things for granted. Instead, always respect and follow the norms in the host country. Unlike my previous courses which were lecture style, the last paper for me to complete was very self-directed. Students bore the responsibility of finding a host organisation to research and conduct their project. Even though there were clear instructions, the expectations seemed daunting. After a few days’ consideration, I finally identified my research topic about Chinese parents’ involvement in the early childhood setting in New Zealand. And it was soon agreed by the lecturer and approved by the University’s Ethics Committee. So, the next step was to locate the host organisation to serve as a base for my research.